Genomic and enzymatic insights into α-amylase-producing Bacillus spizizenii strains isolated from Isfahan province, Iran - Batoul Al Sharif; Mohammad Mehdi Golchini; Aboozar Soorni; Rahim Mehrabi (PLoS ONE, 2025)
Objective α-Amylases represent a class of industrially critical enzymes widely employed in food processing, animal feed, and biotechnology sectors. While microbial sources, particularly Bacillus species, serve as preferred production platforms due to their efficiency and scalability, there remains a pressing need to discover novel strains with enhanced enzymatic properties from underexplored environments. This study investigated the isolation and characterization of high-performance α-amylase-producing bacteria from diverse ecological niches across Iran, including Golestan, Mazandaran, Gilan, Kurdistan, and Isfahan, with particular emphasis on their potential application in animal feed industries. Methods Strains capable of producing amylase were extracted from environmental samples in Iran, subjected to screening through starch hydrolysis, and subsequently optimized for their enzymatic activity. The chosen strains underwent morphological and genetic characterization, including 16S / rpoB and whole-genome sequencing, followed by the purification of the enzyme and in silico analysis. Results Through systematic screening of sixty bacterial isolates obtained from soil, water, and industrial effluent samples, four promising strains were selected based on their superior productivity indices (PI > 1.8) and enzymatic activity profiles. Among these, strains S1 and S3 (isolated from the Kuhrang water source and Gavkhouni Wetland in Isfahan province, respectively) demonstrated exceptional α-amylase production capabilities (reaching 34,121 U/g under optimal conditions) along with remarkable stability across broad pH (4−9) and temperature (30−80°C) ranges. Comprehensive genomic characterization, including whole-genome sequencing and phylogenetic analysis, identified these isolates as novel variants of Bacillus spizizenii , marking the first report of this species’ α-amylase potential from Iranian ecosystems, specifically originating from Isfahan province. Further analysis revealed a 1980 bp GH13-family α-amylase gene encoding a 62 kDa enzyme with 93.6% sequence similarity to AmyE of B. subtilis , while molecular docking studies demonstrated strong binding affinities (−8.4 kcal/mol) with maltotetraose, supported by critical interactions with catalytic residues. Conclusions The combination of robust enzymatic activity, exceptional environmental tolerance, and confirmed genetic basis positions these B. spizizenii strains as highly promising candidates for industrial enzyme applications. This work not only expands the known diversity of high-performance α-amylase producers but also provides valuable insights into the biotechnological potential of underutilized Bacillus species from unique geographical sources.